Proceso para integrar personas y su relación con el desempeño laboral en la Municipalidad Provincial de Maynas, Iquitos año 2018 - Pinedo Saboya, Julio Cesar (2019)
The present investigation entitled: Process to integrate people and their relation with the labor performance in the Provincial Municipality of Maynas, Iquitos year 2018; Its main objective was to establish the relationship between the variables under study, which is why we have opted for a descriptive-correlational type research being of non-experimental design, for which a sample of 101 collaborators has been taken as contracted, to whom a survey was applied using as a tool a questionnaire of questions, arriving in such a way to the following conclusions: It was determined that the process to integrate people is being developed on a regular basis, due to the series of existing shortcomings, it is perceived in which almost never the area informs the head of human resources the need to carry out the process of recruitment of the vacant position, likewise seldom apply means of communication both internally and externally to disseminate information, almost never the institution evaluates the documentation that each candidate has. On the other hand, it was determined that the work performance of the staff is regular, since the employees perform their work with little professionalism, also the service provided has a low frequency of error, almost never the workday brings good results for the organization, rarely The staff does not contribute new ideas and criteria, nor are there constant improvements and fulfillment of responsibilities. Finally it has been determined that there is a direct relationship between the process to integrate people and work performance in the Provincial Municipality of Maynas, Iquitos 2018, alternative hypothesis that has been corroborated by the statistical analysis of Spearman's Rho which showed a coefficient of correlation of 0.845 (positive and significant correlation) and p value equal to 0.000.